Energy-Saving Performance and Optimization Study of Adaptive Shading System—A Case Study - Feining Yang; Huangping Zhou; Jianxing Chen; Yu Sun; Dong Wang; Fengjun Sun; Lili Zhang (Buildings)
In the context of global energy challenges, adaptive shading systems have emerged as pivotal components in building energy efficiency research. This study systematically evaluates critical performance factors influencing energy efficiency in adaptive shading systems for buildings located in hot summer and cold winter climate zones, with a focus on parametric optimization of shading panel configurations. Through field measurements, orthogonal experimental design, and numerical simulations, this investigation centers on the adaptive shading system of a nearly zero energy building (NZEB). Four critical parameters—shading panel width, panel-to-window clearance, window-to-wall ratio (WWR), and surface reflectance—were rigorously analyzed through orthogonal experimental methodology and DesignBuilder® simulations. This study identifies WWR and shading panel reflectance as the key factors for optimizing adaptive shading systems. Among the scenarios evaluated, the highest energy efficiency was achieved with horizontal shading devices on the south façade, featuring a panel width of 500 mm, a minimum clearance of 150 mm, a WWR of 55%, and a surface reflectance of 0.4. Under this configuration, the annual energy consumption was reduced to 8312.37 kWh, corresponding to a 2.1% decrease (8.31 MWh) in total site energy consumption (TSEC). This research provides valuable insights for energy-efficient building design in hot summer and cold winter regions, and supports the broader adoption of adaptive shading systems.